Water storage and irrigation practices for cannabis drive seasonal patterns of water extraction and use in Northern California. (15th October 2020) - Dillis, Christopher; McIntee, Connor; Butsic, Van; Le, Lance; Grady, Kason; Grantham, Theodore
Abstract: There is growing concern over the impacts of cannabis farms on the environment and water resources in particular, yet data on cultivation practices and water use patterns have been limited. Estimates of water use for cannabis cultivation have previously relied on extrapolated values of plant water demand, which do not account for differences in cultivation practices, variation across the growing season, or the role of water storage in altering seasonal extraction patterns. The current study uses data reported by enrollees in California's North Coast Regional Water Quality Control Board Cannabis Program to model how variation in cultivation practices and the use of stored water affect the timing and amount of water extracted from the environment. We found that the supplemental use of stored water resulted in a seasonal pattern of water extraction (water withdrawals from the environment) that was distinct from water demand (water applied to plants). Although water input to storage in the off-season months (November through March) reduced water extraction in the growing season (April through October), farms generally did not have sufficient storage to completely forbear from surface water extraction during the growing season. The most important predictors of storage sufficiency were type of storage infrastructure, type of water source, and farm size, with the likelihood of sufficiency decreasing with increasing cultivation area. As of 2019, state cannabis regulations require forbearance from surface water diversions from April through October. To comply, farms relying on surface water must either develop storage, reduce water demand, or seek alternative water sources, such as groundwater. Our findings indicate that water extraction from farms using groundwater wells generally occurs during the summer dry season and highlight the need to assess their potential impacts to connected surface water in streams. Finally, given that the current study was based on data exclusively from permitted cannabis farms, additional data from unpermitted operations would enhance our overall understanding of cannabis water-use practices and consequences for the environment. Highlights: Irrigation by cannabis farming in California has been cast as a threat to streamflow. Prior methods of estimating water demand of cannabis cultivation are incomplete. Water storage and sources influence extraction patterns and potential stream impacts. Farms in general do not have enough water storage to forbear from summer diversions. Wells will likely become more common, necessitating ground-to-surface water research.